2015
DOI: 10.1111/ans.13373
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinaemia: its utility in non‐perforated appendicitis

Abstract: Bilirubin had a higher specificity than CRP and WCC overall in patients with appendicitis. Hyperbilirubinaemia had a high PPV in patients with simple appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
3
11
0
1
Order By: Relevance
“…One limitation of this study is that it is retrospective and includes a relatively small sample size. However, this is consistent with several retrospective studies of appendixes that analyzed fewer than 200 subjects [ 20 21 22 ]. Another large-scale, multicenter study may yield further outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…One limitation of this study is that it is retrospective and includes a relatively small sample size. However, this is consistent with several retrospective studies of appendixes that analyzed fewer than 200 subjects [ 20 21 22 ]. Another large-scale, multicenter study may yield further outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the sensitivity of direct bilirubin in detecting complicated appendicitis was 98.17%. Sandstrom et al [12] reported that similar to the literature, the bilirubin values provided more significant results in complicated appendicitis than CRP and leukocytes, but the PPV values were higher in AUA cases. Eddama et al [2] found that bilirubin, leukocyte, and CRP were correlated with each other in AUA, but the same correlation was not observed in individuals with normal pathology findings and those with complicated appendicitis.…”
Section: Discussionsupporting
confidence: 55%
“…We set cut-off scores for WBC count, CRP level, fever, and total serum bilirubin level at 11,000/μL, 0.5 mg/dL, 37.3°C, and 1.1 mg/dL, respectively, based on previous reports. 3,7,8…”
Section: Methodsmentioning
confidence: 99%